Karakteristik Butir Soal Tes Logika Matematika Dan Himpunan Ditinjau Dari Teori Tes Klasik - Fahmi, Syariful; Priwantoro, Soffi Widyanesti; Prabowo, Anggit (Universitas Pekalongan, 2025)
This study aims to analyze the formative test items for the Mathematical Logic and Sets course in the Digital Innovation Program of the Mathematics Education Study Program, FKIP UAD in terms of classical test theory. This research is descriptive research. The analysis was carried out on 20 multiple choice test items which were tested on 51 students. The analysis was carried out on the difficulty and discrimination index and reliability with the help of the ITEMAN (Item and Test Analysis) package program. The results of the analysis of the difficulty index showed that of the 20 items, there were 6 items that were difficult and 14 items that were moderate. In terms of discrimination, 18 items had good discrimination index and only 2 items had poor discrimination index. One of the causes of low discrimination index is caused by items that are too difficult. From these results, further revisions were made to the items that did not meet the good criteria. Reliability estimation using the Cronbach Alpha formula shows that the measurement results obtained through this test are reliable.